Deciphering the role of Hashimoto's Thyroiditis-related key genes in thyroid cancer via detailed in silico analysis followed by the experimental validation - Mostafa A. Abdel-Maksoud; Taghreed N. Almana; Saeedah Almutair; Abdulaziz Alamri; Ibrahim A. Saleh; Mohamed Y. Zaky; Wahidah H. Al-Qahtani; Yasir Hameed (Hereditas)
Abstract Background Thyroid cancer, characterized by significant genetic and epigenetic alterations, remains a critical focus of molecular oncology. This study investigates eight key genes (BRAF, EIF1 AX, FOXE1, KRAS, PDGFRA, PIK3 CA, PTEN, and TERT) that are deregulated in Hashimoto's Thyroiditis and their roles in thyroid cancer. Methods Cell culture, nucleic acid extraction, RT-qPCR, bisulfite sequencing, and various in silico tools and databases. Results Expression analysis using RT-qPCR revealed significant (p-value < 0.05) down-regulation of BRAF, EIF1 AX, FOXE1, KRAS, PDGFRA, PIK3 CA, PTEN, and TERT genes in thyroid cancer cell lines compared to controls, with ROC curves indicating high diagnostic accuracy (AUC 0.93–0.99). Bisulfite sequencing demonstrated increased promoter methylation across all eight genes in cancerous samples, suggesting epigenetic silencing as a regulatory mechanism. Validation through UALCAN, OncoDB, and HPA confirmed reduced gene and protein expression in additional thyroid cancer cohorts. Genetic alteration analysis via cBioPortal showed prevalent BRAF mutations, whereas other genes exhibited fewer alterations. Kaplan–Meier survival analysis linked lower expression of BRAF and PIK3 CA to poorer overall survival. Correlation studies using TISIDB and TISCH2 databases highlighted associations between gene expression and immune modulation, revealing significant correlations with immune cell infiltration and diverse immune subtypes. Moreover, miRNA-mRNA network analysis identified hsa-mir- 628 - 5p as a critical regulator targeting these genes. The impact of BRAF overexpression on SW579 cells was assessed through various functional assays. Overexpression of BRAF resulted in reduced cell proliferation, colony formation, and wound healing, which may reflect context-dependent effects. While BRAF is typically oncogenic, its overexpression may lead to cellular stress or negative feedback mechanisms that impair these processes. Conclusion This comprehensive analysis elucidates the complex regulatory landscape of these genes in thyroid cancer, emphasizing the significant role of epigenetic modifications and providing insights into potential diagnostic and therapeutic avenues.